Avaliação do potencial nutricional e antioxidante de variedades de quinoa (Chenopodium quinoa willd.) - Polari, Isabelle de Lima Brito (2017)
Quinoa (Chenopodium quinoa Willd.) is considered a food with functional properties because it contains compounds that are associated with several health benefits. Considering the growing interest in the use of these seeds in the prevention of diseases and their potential for food industry, the present study offers initially scientific approaches, in the form of a bibliographic review highlighting the nutritional characteristics, technological and the physiological benefits associated with the consumption of quinoa in different types of diseases. The quinoa seeds, in the white and red variety, cultivated in Brazil and Bolivia were evaluated for their nutritional profiles and antioxidant activity, as well as their respective oils. The degreased seeds were analyzed through an experimental design, regarding the extraction conditions of phenolic compounds and antioxidant activity. A first order polynomial model was designed to evaluate the effects of the independent variables: temperature (32-68 ° C), time (6.5-19.5 h) and ethanol concentration (19-76%) on the extraction of total phenols (TFT), antioxidant activity (DPPH, FRAP, ABTS) and identification and quantification of phenolics by high performance liquid chromatography. The optimal extraction conditions were analyzed using response surface methodology and obtained through the simultaneous maximization of the analyzed parameters. For the Brazilian white variety the maximum point of planning (68 ° C, 19.5 h, 76 % ethanol) obtained the highest responses for TFT, ABTS and phenolic concentration. Already for the white Bolivian, in the minimum conditions (32 ° C, 6.5 h, 19% ethanol) greater TFT and DPPH were identified; however, for the quantification of phenolics, the maximum conditions of temperature and ethanol concentration obtained higher responses (68 ° C, 6,5h, 76% ethanol). For Bolivian red quinoa, these same conditions were responsible for the statistically significant responses for all dependent variables and phenolic concentration. Among phenolic acids, 2,5-dihydroxybenzoic, synapic, ferulic, salicylic and ellagic and, flavonoids, kampferol, myricetin, quercetin, catechin and rutin as the major, were the compounds responsible for the high antioxidant activity of the seeds. The statistical model demonstrated relevance in the use of the "green" solvent mixture in the extraction of phenolics from quinoa seeds. Similarly, the in natura oils extracted from the seeds presented high oxidative stability, with an induction period of up to 8.11 hours. The oils also obtained important importance as to the antioxidant capacity, so it was only necessary 7.65; 6.81 and 6.07 µL of the oils of the Brazilian, Bolivian and Bolivian red varieties respectively, to eliminate 50% of the DPPH free radical. It was also identified polyunsaturated fatty acids, presence of essential amino acids and nutritionally important minerals such as magnesium, manganese, iron and selenium in the constitution of the seeds. The white quinoa of Brazil was highlighted as to its nutritional quality compared to the other seeds analyzed. Therefore, the present study confirmed quinoa as a high antioxidant capacity food, with potential for use in health promotion and for the food industry.